High-risk myeloma and minimal residual disease postautologous-HSCT predict worse outcomes. Issue 2 (28th January 2019) - Hu, Bei; Thall, Peter; Milton, Denái R; Sasaki, Koji; Bashir, Qaiser; Shah, Nina; Patel, Krina; Popat, Uday; Hosing, Chitra; Nieto, Yago; Lin, Pei; Delgado, Ruby; et al.
Abstract: The aim of our study was to determine the impact of high-risk disease (HRD) and MRD on outcomes in myeloma patients receiving bortezomib-based induction followed by autologous hematopoietic stem cell transplant (auto-HSCT). HRD included t(4:14), t(14;16), del 17p, del 1p and/or amplification 1q by cytogenetics/FISH; all others were standard-risk disease (SRD). A subset of 165 newly diagnosed myeloma patients in a 2:1 ratio of HRD:SRD was generated using propensity score based nearest neighbor matching. Multiparametric flow cytometry (MFC) was used to detect MRD after auto-HSCT in select patients. MRD+ status at 3 months post auto-HSCT (hazard ratio (HR = 4.23, p  = .028) and HRD (HR = 1.72, p  = .026) were associated with a shorter PFS. Similarly, MRD+ 3 months post auto-HSCT (HR = 6.93, p  = .08) and HRD (HR = 3.54, p  < .001) and were associated with a shorter OS. Despite bortezomib-based induction, upfront auto-HSCT, and use of maintenance therapy, PFS and OS remained worse in MRD+ and HRD patients.